Pengaruh Relaksasi Otot Progresif terhadap Perubahan Kadar Gula Darah pada Pasien Diabetes Melitus di Rs Trimitra - Tommy Jeremi Wowor; Susanti Widiastuti; Widia Rahmayanti (Universitas Malahayati Lampung, 2023)
ABSTRACT Diabetes Mellitus (DM) is a progressive chronic disease characterized by the body's weakness to separate carbohydrate, fat and protein metabolism, resulting in hyperglycemia or high blood glucose levels (Black Hawk, 2014).To analyze the effect of progressive muscle relaxation on changes in blood sugar levels in patients with diabetes mellitus at Trimitra Cibinong Hospital, Bogor.The method used is Quasi Experiment with pre-experimental design type one group pretest-posttest with control (initial test, single group end test). From the results of the Wicoxon test, the symp.Sig value for the intervention group before and after was 0.025 ( 0.05) so it could be interpreted that there was a significant effect or difference in blood sugar levels after the Progressive muscle relaxation intervention. Meanwhile for the control group, there is a symp.Sig value of 0.317 ( 0.05), which means that there is no significant effect or difference in checking blood sugar levels. And to see the difference or distinction mean among ke-2 group so using the data because withney knowledge not normally distributed with the results obtained value asym.sig is 0,037 (0,05) thus differences in and there an effect the techniques of relaxation progressive muscle. on changes in blood sugar levelsThere is a significant difference or effect on Blood Sugar Levels in the Intervention Group before (pre-test) and after (post-test) muscle relaxation is performed, while Blood Sugar Levels in the Control group There is no significant difference or effect, To achieve the results Nurses can provide patient education on how to do good and regular progressive muscle relaxation techniques to achieve normal changes in blood sugar levels. Keywords: Diabetes Mellitus, Progressive Muscle Relaxation, Blood Sugar Level ABSTRAK Diabetes Mellitus (DM) adalah penyakit kronis progresif yang ditandai dengan kelemahan tubuh untuk melakukan pemisahan metabolisme karbohidrat, lemak dan protein, sehingga mengakibatkan hiperglikemia atau kadar glukosa darah yang tinggi (Black Hawk, 2014). Tujab penelitian ini adalah Menganalisa pengaruh relaksasi otot progesif terhadap perubahan kadar gula darah pasien diabetes melitus di RS Trimitra Cibinong Bogor. Metode yang digunakan adalah Quasi Eksperiment dengan pre- experimental design tipe one group pretest-posttest with kontrol (tes awal tes akhir kelompok tunggal).Dari hasil uji Wilcoxon didapat hasil nilai Asymp.Sig untuk kelompok Intervensi sebelum dan sesudah bernilai 0,025 ( 0.05) maka dapat diartikan bahwa ada Pengaruh atau perbedaan Kadar Gula Darah yang signifikan setelah dilakukan intervensi relaksasi otot Progresif. Sedangkan untuk Kelompok Kontrol terdapat nilai symp.Sig 0.317 ( 0.05) yang artinya tidak ada Pengaruh atau perbedaan pengecekan Kadar Gula Darah yang signifikan. Dan untuk melihat selisih atau perbedaan mean di antara ke-2 kelompok menggunakan uji Mann Withney karna data yang didapatkan tidak terdistribusi dengan normal dengan hasil didapatkan nilai Asym.Sig adalah 0,037 (0,05) dengan demikian adanya perbedaan dam ada pengaruh pemberian teknik relaksasi otot progresif terhadap perubahan kadar gula darah. Kata Kunci: Diabetes Melitus, Relaksasi Otot Progresif, Kadar Gula Darah